V All-Russian Demographic Forum - T. K. Rostovskaya; Yu. N. Ebzeeva (RUDN journal of Sociology)
In the year of the 300th anniversary of the Russian Academy of Sciences and the Year of the Family in Russia, the V All-Russian Forum with international participation was held in the Krasnodar Region (Sochi) with the support of the RUDN and the Ministry of Labor and Social Protection. This Forum has been held since 2019 by the Institute for Demographic Research of the Federal Center of Theoretical and Applied Sociology of the Russian Academy of Sciences. The Forum aimed primarily at assessing demographic situation at the national and international levels in 2023-2024 and at developing new approaches to the implementation of demographic policies for increasing birth rate, forming motivation for having many children and healthy longevity, regulating the labor market and migration processes. The plenary and sectional sessions consisted of presentations by the heads of federal and regional government bodies, leading Russian and foreign scientists in the field of demography, and of the “Demographic Encyclopedia in Persons. Vol. 1. Pre-Revolutionary Period” and the National Report for 2023 “Demographic Well-Being of Russian Regions”. Two thematic issues of the journals Higher Education in Russia (No. 8) and Issues of Management (No. 3) were published for the Forum.